2021
DOI: 10.3390/antiox10111665
|View full text |Cite
|
Sign up to set email alerts
|

Organic Acids Improve Growth Performance with Potential Regulation of Redox Homeostasis, Immunity, and Microflora in Intestines of Weaned Piglets

Abstract: The objective of this study is to evaluate the effects of organic acids on piglet growth performance and health status. A total of 360 weanling pigs (5.3 ± 0.6 kg) were randomly allotted to 3 treatment groups with 12 replicates of 10 pigs/pen. Piglets were fed the same basal diet and given either water (control) or water plus 2.0 L/Ton organic acid (OA) blends, such as OA1 or OA2, respectively, for 7 weeks. Compared to the control, OA1 and OA2 improved growth performance and/or reduced the piglets’ diarrhea ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Therefore, total antioxidant capacity is of great significance to scientifically evaluate the antioxidant capacity of antioxidant substances. In the present study, DQ increased ROS and MDA levels in IPEC-J2 cells, while the acidifiers decreased the levels of ROS and MDA by reversing the decrease in T-SOD and GSH-Px, suggesting that the acidifiers have potential antioxidant effects under cellular oxidative stress, which is consistent with previous studies [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, total antioxidant capacity is of great significance to scientifically evaluate the antioxidant capacity of antioxidant substances. In the present study, DQ increased ROS and MDA levels in IPEC-J2 cells, while the acidifiers decreased the levels of ROS and MDA by reversing the decrease in T-SOD and GSH-Px, suggesting that the acidifiers have potential antioxidant effects under cellular oxidative stress, which is consistent with previous studies [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, in our study, we found that the average relative abundance of Firmicutes in the Dia of the large intestine was lower than that in the Con, which may be due to the disordering of intestinal barrier function after the cessation of antibiotics due to the disordering of amino acid metabolism. At the same time, previous studies have also shown that the high abundance of bacteria involved in amino acid metabolism in Firmicutes can enhance intestinal mucosal immunity, and reduce intestinal oxidative stress and the diarrhea rate of piglets [ 61 , 62 ]. Therefore, the decrease in Firmicutes abundance in Dia may be due to the specific strains involved in amino acid metabolism reducing intestinal mucosal immunity and increasing intestinal oxidative stress levels.…”
Section: Discussionmentioning
confidence: 99%
“…The HCL secretion function of gastric oxyntic cells is not yet perfect in weaned piglets at the early stage of weaning [ 68 ]. A higher pH value is considered harmful because it has been shown to increase the numbers of pathogenic bacteria and decrease SCFA production [ 69 ]. Moreover, MOLP may produce toxic ammonia–nitrogen metabolites, such as spermidine, histamine, and putrescine, leading to an increased diarrhea rate after weaning [ 70 ], thus masking the beneficial effects of fiber fermentability on weaned piglets.…”
Section: Discussionmentioning
confidence: 99%